A detrital apatite fission‐track study of the CIROS‐2 sedimentary record: Tracing ice pathways in the Ross Sea area over the last 5 Ma. (6th May 2019) - Li, Xia; Zattin, Massimiliano; Olivetti, Valerio
Abstract: The Ross Sea is a crucial area to investigate pathways of ice during the Cenozoic as it records the evolution of both the East and West Antarctic Ice Sheets. This work is based on detrital apatite fission track (AFT) data extracted from the sedimentary record of well CIROS‐2, which spans the last 5 Ma. The AFT data show a large range of ages, and most of the grains fit well with two main components that fall between 24 and 42 Ma and between 43 and 70 Ma, whereas the other components are not regularly distributed through the well, thus indicating a mixture of provenance from different areas along the Transantarctic Mountains. As a whole, our work suggests glacial expansion over the McMurdo Sound during the Pliocene, and ice periodically invading and retreating in Pleistocene.